Tillage and Crop Residue Management Practices for Sustainable Dryland Farming Systems - Unger, Paul W; Schomberg, Harry H; Dao, Thanh H; Jones, Ordie R (Annals of Arid Zone, 2016)
Dryland crop production is limited by precipitation and by soil factors such as texture and profile depth that affect water storage capacity, pH, fertility, and salinity. When prevailing precipitation and soil factors are not in balance, crops will not yield at their potential and productivity may be impaired because soil degradation processes outweigh conservation practices. Sustainable crop production is possible through use of appropriate tillage and crop residue management practices. When adequate crop residues are available, conservation tillage is highly effective for conserving soil and water, achieving favorable crop yields, maintaining soil organic carbon contents, and soil and water quality. Other tillage methods along with appropriate conservation practices may be needed when crop residues are limlited.